Control of Ventricular Ciliary Beating by the Melanin Concentrating Hormone-Expressing Neurons of the Lateral Hypothalamus: A Functional Imaging Survey - Conductier, Gregory; Martin, Agnès; Risold, Pierre-Yves; Jégo, Sonia; Lavoie, Raphaël; Lafont, Chrystel; Mollard, Patrice; Adamantidis, Antoine; Nahon, Jean-Louis (Frontiers in Endocrinology, 2013)
The cyclic peptide Melanin Concentrating Hormone (MCH) is known to control a large number of brain functions in mammals such as food intake and metabolism, stress response, anxiety, sleep/wake cycle, memory, and reward. Based on neuro-anatomical and electrophysiological studies these functions were attributed to neuronal circuits expressing MCHR1, the single MCH receptor in rodents. In complement to our recently published work (1) we provided here new data regarding the action of MCH on ependymocytes in the mouse brain. First, we establish that MCHR1 mRNA is expressed in the ependymal cells of the third ventricle epithelium. Second, we demonstrated a tonic control of MCH-expressing neurons on ependymal cilia beat frequency using in vitro optogenics. Finally, we performed in vivo measurements of CSF flow using fluorescent micro-beads in wild-type and MCHR1-knockout mice. Collectively, our results demonstrated that MCH-expressing neurons modulate ciliary beating of ependymal cells at the third ventricle and could contribute to maintain cerebro-spinal fluid homeostasis.